The Daanish Schools: To Expand or Not to Expand!. (September 2013) - Qureshi, Zafar I.; Jilani, Hira I.
The case discusses the Daanish School System (DSS) as an innovative education system for the marginalized children of southern Punjab. The English equivalent of Daanish (an Urdu word) means 'wisdom'. The Chief Minister (CM) of the province of Punjab had asked Mr Iqbal Qureshi, Chairman, Core Group of the Daanish School & Centre of Excellence Authority (DS&CEA), to recommend a strategy to expand DSS further and to ensure its financial sustainability as opposed to the upgradation of the existing public sector schools. The opponents of DSS were supporting the latter, while there were others who supported DSS expansion. The core group was also divided on the expansion strategy into two sub-groups: one sub-group was supporting the expansion strategy, whereas the other sub-group was not. In parallel, the core group was also expected to suggest steps to ensure future sustainability of DSS.